High contrast visualization of cell-hydrogel contact by advanced interferometric optical microscopy - Matsuzaki, Takahisa; Sazaki, Gen; Suganuma, Masami; Watanabe, Tatsuro; Yamazaki, Takashi; Tanaka, Motomu; Nakabayashi, Seiichiro; Yoshikawa, Hiroshi Y. (The journal of physical chemistry letters, 2014)
Hydrogels with tunable elasticity has been widely used as micromechanical environment models for cells. However, the imaging of physical contacts between cells and hydrogels with a nanometer resolution along the optical axis remain challenging because of low reflectivity at hydrogel-liquid interface. In this work, we have developed an advanced interferometric optical microscopy for the high contrast visualization of cell-hydrogel contact. Here, reflection interference contrast microscopy (RICM) was modified with a confocal unit, high throughput optics and coherent monochromatic light sources to enhance interferometric signals from cell-hydrogel contact zones. The advanced interferomety clearly visualized physical contacts between cells and hydrogels, and thus enabled the quantitative evaluation of the area of cell-hydrogel adhesion.